Impact of the United Nations Sustainable Development Goals on the Comprehensive Progress of the United States, México, and Canada - Pena-Sanchez, Rolando (Archives of Business Research, 2022)
In this article, we describe the impact of the United Nations Sustainable Development Goals on the integral progress of the United States, México, and Canada, which brings multiple benefits to all institutions, communities, and individuals in the mentioned countries, which since 1989 had signed a free trade agreement (NAFTA), now replaced by a new commercial treaty (USMCA) entered in operations in 2020. The United Nations Department of Economic and Social Affairs established 17 Sustainable Development Goals in 2015, whose scopes are projected to be fulfilled before 2030. Among the 17 compared objectives, only two, the Goal-1 (End poverty in all its forms everywhere), and Goal-4 (Ensure inclusive and equitable quality education and promote lifelong learning opportunities for all) showed significant differences (p-value=0.012, and 0.001 respectively) via an analysis of variance (ANOVA) for the average achievement % distribution per Goal between countries. We hope that this essay can contribute in some way to the awakening of consciences for sustainable development.